Morphological and Histological Study of Uropygial Gland in Moorhen (G. gallinula C. choropus) - Sawad, A.A. (International Journal of Poultry Science, 2006)
Eighteen healthy moorhens obtained to describe the anatomical and histological structures of uropygial glands. The gland in moorhen composed of two lobes, each one has a single uropygial duct and they joined together by isthmus. Uropygial gland is embedded beneath the skin in a mass of fatty tissue, they surrounded by a connective tissue capsule apparently devoid of muscle fibers and receives its blood supply from the caudal artery, and drained by the caudal vein. The gland parenchyma consist of a highly developed trabeculae packed with tiny parallel secretary tubules, smooth muscle fibers are founds around these trabeculae and also forms a sphincter at the nipple of excretory ducts.